Performance analysis of facts devices for reduction of power quality issues in DFIG based WECS integrated to grid - Rama Sekhar Reddy, M; M. Vijaya Kumar, Dr (International Journal of Engineering and Technology, 2018)
Integration of a wind farm with electric grid is an issue that has gained interest due to poor power quality and unmatched power and frequency of grid. Maintenance of power quality has become an important factor in modern power systems. The usage of non-linear loads results in various power quality events which over a period would reduce life and deteriorate the performance of end user equipment. FACTS devices are available that use power electronic components provide efficient solutions for improving power quality in Distribution systems. This paper discusses performance of three FACTS devices SSSC, DSTATCOM and UPQC for mitigating voltage sags, swells and harmonics injected into a DFIG based WECS. The model is developed on MATLAB/ SIMULINK platform and results are presented.Â Â